Environmental engineering education in Canada. Issue 1 (1st February 2002) - Smith, Daniel W; Biswas, N
Abstract : Environmental engineering education has been an active option for engineers from all disciplines for nearly 50 years at the graduate level. Some graduate programs expanded to integrate students with undergraduate science degrees with the engineering programs, since the cross discipline interaction is required outside the academic programs. In the mid-1980s interest increased to such a level that undergraduate programs began to form. Several of these programs have been accredited in their various forms recognizing the diversity of the field and those presenting the programs. The progression from graduate-degree-based specializations to broad-based undergraduate programs reflects both the increased knowledge in the field and the increased demand for professional engineers capable of responding to public health and environmental protection issues. Graduate programs greatly expand fundamental knowledge of physical, chemical, and biological processes and their application to protection problems. Of course, the doctorate is dedicated to the development of significant new knowledge. This paper defines several of the basic components of the environmental engineering profession and the educational process needed to produce qualified environmental engineers. Key words : environmental engineering, education, courses, undergraduate environmental engineering, graduate environmental engineering.